Potential predators of Asian citrus psyllid, Diaphorina citri, vector of Huanglongbing, in different flushing patterns - Calgaro, Giovanni; Saluso, Adriana; Cuatrin, Alejandra; Bouvet, Juan Pedro (Facultad de Ciencias Agropecuarias, Universidad Nacional de Entre Ríos (UNER), 2024)
Póster de la presentación